RsmN : a new atypical RsmA homologue in Pseudomonas aeruginosa - Lovelock, Laura Charlotte (2012)
The RsmA/CsrA family of global post-transcriptional regulators are small RNA-binding proteins involved in the regulation of a large number of genes such as those involved in quorum sensing, virulence factor production, secondary metabolism, motility and biofilm formation. They bind to target mRNAs and hence modulate their stability and translation rates. Their effects are antagonised by small non-coding regulatory RNAs. The control of expression of target genes via this post-transcriptional regulatory network is mostly operated in Pseudomonas spp. via the GacS/GacA two component system. This study aimed to perform a biophysical analysis of RsmA and to obtain a preliminary understanding of the structure, function and regulation of RsmN, a new atypical RsmA homologue from Pseudomonas aeruginosa. RsmA was purified and biophysical analysis confirmed that RsmA exists as a dimer and is highly stable at high temperatures (75 °C) and low pH (5.2). Although RsmN was found to be structurally similar to RsmA, no functional phenotypes have been identified. Consequently, rsmN was mutated and transcriptional fusions to rsmN and its anti-sense transcript were constructed for expression studies. Phenotypic analysis indicated that RsmN was not involved in the control of swarming, pyocyanin, elastase and protease production or glycogen accumulation. Unlike RsmA, RsmN does not have a control on the restriction modification system of P. aeruginosa. Transcriptional fusions revealed RetS, LadS and GacA all appear to have a 21 significant effect as activators of both the rsmN and nmsR promoters. 2-Alkyl-4(1H)-quinolone (AQ) signalling also modulate rsmN expression possibly via the iron chelating properties of 2-alkyl-3-hydroxy-4(1H)-heptyl-quinolone (PQS). RsmN targets identified from Deep Sequencing include those required for structural outer membrane proteins, transcriptional regulators as well as genes involved in motility, secretion, flagellar structure and biofilms. RsmA, RsmZ and RsmY were all identified as targets together with the small RNAs RgsA (indirectly gac-controlled) and the antagonistic RNA CrcZ (represses catabolite repression control protein Crc). Targets common to both RsmN and RsmA include the transcriptional regulators Vfr, PqsR, MvaT and Anr, regulatory RNAs RsmZ and RsmY together with transcripts corresponding to the pqsABCDE operon, LasB, LecA/B, RhlI, LasR/I, Crc and CrcZ. The identification of many mRNA targets for RsmN which are shared with targets of RsmA provides further evidence that RsmN is involved in global-post-transcriptional regulation of gene expression.